ECONOMIC OPPORTUNITIES AND READINESS OF THE CITY OF BALIKPAPAN: TRAILS TOWARDS THE NATIONAL CAPITAL AND THE SMART CITY ERA - Kurniadi, Agus; Markhamah, Siti (Nusantara Economics and Entrepreneurships Journals, 2024)
The city of Balikpapan has a strategic position as the main gate to the new capital city. This opportunity has a positive impact on the growth of Balikpapan City, especially in encouraging investment. The aim of this research is to determine the economic potential and readiness of Balikpapan City as the home of the National Capital with the development of a smart city. The method in this research uses a qualitative and quantitative approach, the data used is primary data and secondary data, data collection uses a questionnaire distribution technique (Likert scale) with snowball sampling. Data analysis techniques use descriptive analysis and Location Quotient (LQ) analysis. The results of this research show that from the economic aspect in Balikpapan City, this research identified a number of main sectors, such as processing industry, electricity and gas procurement, water supply, waste management, waste and recycling, construction, wholesale and retail trade, car repair and motorbikes, transportation and warehousing, provision of accommodation and food and beverage, information and communications, financial services and insurance, real estate, and other service sectors. The challenges faced by the City of Balikpapan as the home of the National Capital with the development of a smart city involve implementation that is not yet optimal, becoming an obstacle in increasing economic growth and the quality of life of the community. Apart from that, other problems include increasing waste volumes and narrowing waste storage areas in Balikpapan City